2008
DOI: 10.1086/524054
|View full text |Cite
|
Sign up to set email alerts
|

X‐Ray Spectroscopy of the 2006 Outburst of RS Ophiuchi

Abstract: We present X-ray grating spectra of the recurrent nova RS Ophiuchi during its 2006 outburst, obtained with XMMNewton and Chandra. For the first month after optical maximum, the X-ray spectrum was hard and dominated by emission lines of H-like and He-like ions. The X-ray luminosity was 2:4 ; 10 36 ergs s À1 in the 0.33Y10 keV range. The spectra indicate a collisionally dominated plasma with a broad range of temperatures and an energy-dependent velocity structure. During an observation obtained in week 4, a soft… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
151
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(172 citation statements)
references
References 33 publications
(30 reference statements)
19
151
2
Order By: Relevance
“…The best-fit models use a blackbody temperature (T BB ) of 5.8 × 10 5 K and 5.5 × 10 5 K and a luminosity of 6.3 × 10 38 ergs s −1 and 8.0 × 10 38 ergs s −1 , respectively, on D31 and D49. This is in agreement with the WD temperature of around 8 × 10 5 K derived from x-ray studies by Nelson et al (2008). The low χ 2 red values of 1.2 and 1.8 for the two dates, respectively, indicate that the fits are satisfactory.…”
Section: Resultssupporting
confidence: 89%
“…The best-fit models use a blackbody temperature (T BB ) of 5.8 × 10 5 K and 5.5 × 10 5 K and a luminosity of 6.3 × 10 38 ergs s −1 and 8.0 × 10 38 ergs s −1 , respectively, on D31 and D49. This is in agreement with the WD temperature of around 8 × 10 5 K derived from x-ray studies by Nelson et al (2008). The low χ 2 red values of 1.2 and 1.8 for the two dates, respectively, indicate that the fits are satisfactory.…”
Section: Resultssupporting
confidence: 89%
“…Two recurrent novae with massive WDs of unknown composition were observed using gratings while they were relatively hard X-ray sources. RS Oph did not show very strong lines of Mg and Al, (Nelson et al 2008;Ness et al 2009), consistently with the ultraviolet spectra of a previous outburst (Contini et al 1995). V745 Sco was observed as a hard X-ray source with NuSTAR (Orio et al 2015) and shortly later it was observed it with the Chandra HETG.…”
Section: V959 Mon a Nova Discovered As A Gamma-ray Sourcesupporting
confidence: 85%
“…The XMM-Newton observation taken on day 26.1 is also dominated by the early shock emission, but has an additional soft component that appeared during the observation. Nelson et al (2008) reported that a 35 s period was present during a short time when the soft count rate rapidly increased by a factor 3, and in Fig. 1.…”
Section: Rs Ophmentioning
confidence: 84%
“…So far, no convincing identifications were found after investigating possibilities of extreme line shifts (Nelson et al 2008) or exotic elemental abundances (Orio et al 2010).…”
Section: Rs Ophmentioning
confidence: 99%